Thermal Activation and Deactivation of Ni‐Doped Ceria Catalysts in CO2 Methanation - Mathias Barreau; Davide Salusso; Jinming Zhang; Michael Haevecker; Detre Teschner; Anna Efimenko; Elisa Borfecchia; Kamil Sobczak; Spyridon Zafeiratos (Small Science)
Discovered almost 130 years ago by P. Sabatier, CO2 hydrogenation to methane (CO2 methanation) is presently attracting attention as one of the most promising methods for storing intermittent renewable energy in the form of chemical fuels. Ni particles supported by CeO2 constitute a very effective, reliable, and reasonably priced catalyst for CO2 methanation. Recently a new type of CO2 methanation catalyst, consisting of cerium oxide (ceria) nanoparticles doped with nickel (NiCeOx) in a specific square‐planar configuration with an extremely high‐Ni mass‐specific activity and almost 100% CH4 selectivity, was reported. Here, a 50% enhancement in the CO2 conversion of the NiCeOx catalyst by carefully adjusting the calcination temperature is demonstrated. Notably, thermal aging at 600 °C enhances methanation performance by partially exsolving Ni to the surface, while higher temperatures (750 °C) lead to larger Ni particles, increased CO production, and surface carbon deposition. Several in situ and operando characterization methods are employed to correlate the thermal activation and deactivation of the catalyst with its nanoscale characteristics. Apart from their clear implications for the design of next‐generation Ni‐based CO2 methanation catalysts, these findings significantly enhance understanding of the complex interplay and nature of various surface sites involved in CO2 hydrogenation.